AN RINVR SCORING EVALUATION OF ONDANSETRON, DEXAMETHASONE, AND RANITIDINE AS ANTIEMETICS IN BREAST CANCER CHEMOTHERAPY - FITRIA, NAJMIATUL; RIVALDI, RONA SALSABILA; PERMATASARI, DITA (International Journal of Applied Pharmaceutics, 2025)
Objective: Antiemetics is used to control Chemotherapy-Induced Nausea and Vomiting (CINV) in breast cancer patients undergoing ACTH (Adriamycin, Cyclophosphamide, Docetaxel, Herceptin) chemotherapy. This study aimed to assess the effectiveness of an antiemetic regimen consisting of Ondansetron, Dexamethasone, and Ranitidine combination using (Rhodes Index Nausea Vomiting and Retching) RINVR scoring. Additionally, to evaluate the difference in CINV incidence in ACTH cycles. Methods: A prospective cross-sectional study was conducted from March to June 2024 at Dr. M. Djamil. General Hospital Padang. The study determined the effect of antiemetic administration at the measurement time of 12 h, 24 h, 48 h, 72 h, and 96 h after chemotherapy. There were 30 respondents who met the inclusion criteria in this study. The instrument RINVR (Rhodes Index Nausea Vomiting and Retching) measured the vomit and nausea incidence. Results: There were differences in the incidence of emesis between ACH dan TH cycles at measurement times of 12 h, 48 h, and 72 h (p-value<0.05). The effect of antiemetic administration showed significant results in the 48 h ACH cycle, which indicates that the higher the cycle, the lower the RINVR score. Conclusion: The administration of antiemetics was notably effective at the 48 h mark in the ACH cycle, demonstrating a correlation between higher chemotherapy cycles and lower RINVR scores. These findings highlight the importance of tailored antiemetic strategies to improve patients' comfort and treatment outcomes.